2015
DOI: 10.1128/aac.01017-15
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Entecavir Therapy Is Not Effective for HBeAg Seroconversion in Treatment-Naive Chronic Hepatitis B Patients with a Partial Virological Response

Abstract: The aims of this study were to investigate the efficacy of prolonged entecavir (ETV) therapy in treatment-naive chronic hepatitis B (CHB) patients and to determine whether continuous ETV therapy is feasible to achieve HBeAg seroconversion, particularly in patients with partial virological response (PVR). A total of 142 treatment-naive patients with CHB were enrolled. The mean duration of treatment was 65 (range, 26 to 90) months, and 86 patients (60.6%) were HBeAg positive. PVR was defined as detectable hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Similarly, in an earlier study prolonged ETV therapy was not found very effective in achieving HBeAg seroconversion in treatment-naive CHB patients with a partial virological response. In their study partial virological response was defined as detectable HBV DNA (> 116 copies/mL) at year one [ 28 ]. The two cases received consolidation treatment for 1 year after confirming HBeAg seroconversion on two different occasions 3 months apart.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in an earlier study prolonged ETV therapy was not found very effective in achieving HBeAg seroconversion in treatment-naive CHB patients with a partial virological response. In their study partial virological response was defined as detectable HBV DNA (> 116 copies/mL) at year one [ 28 ]. The two cases received consolidation treatment for 1 year after confirming HBeAg seroconversion on two different occasions 3 months apart.…”
Section: Discussionmentioning
confidence: 99%
“…This is shown in other reports also [7]. Loss of HBsAg is rare [16,18]. There were some drawbacks of our study.…”
Section: Discussionmentioning
confidence: 39%
“…Our study showed maximum decline in HBV DNA starting earlier at 6 months which may be due to the lesser number of cirrhotics and good drug compliance. The high rate of HBV DNA negativity at 1 year (85.7 % [11], 96 % [12], 86.1 % [13]) and after prolonged therapy (92 % at 5 years [3], 95 % at 39 months [14], 83.7 % at 4 years [15], 98.2 % at 7 years [16]) is reflected in many other Asian studies. Studies from other parts of the world show that with 3-5 years of entecavir administration, the serum HBV DNA negativity rate was 55 % to 88 % at 1 year, 83 % to 93 % at 2 years, 89 % to 95 % at 3 years, 91 % to 96 % at 4 years and 94 % at 5 years.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 17 In an ETV 7-year treatment study, HBeAg/anti-HBe seroconversion rates at years 3 and 7 were 26.7% and 37.5%, respectively. 18 Additionally, many investigations have shown that ETV and LDT have a higher rate of HBeAg/anti-HBe seroconversion in patients with HBeAg-positive CHB. 19 24 Therefore, in an analysis of the efficacy of long-term antiviral drug therapy, the combination response showed no strong trend with the virological response or chemical remission.…”
Section: Discussionmentioning
confidence: 99%